Proposta de gestão local de redes sociotécnicas: estratégia para implantação de Cidades Inteligentes e Humanas - Martinelli, Marcos Alberto (Universidade Federal de São Carlos, 2019)
The Science, Technology, and Innovation (ST&I) triad is considered to be the engine of economic growth and, in the Brazilian case, the easing of national policies for ST&I allows sub national regions (states and municipalities) to recognize institutionally their local innovation system. Given the advancement of information and communication technologies, the innovation ecosystem is configured as a sociology-technical network whose assets can be distributed locally, regionally, nationally or internationally, surpassing zone-based development models, clusters and other forms of production arrangements inspired in English industrial districts. Sustainable local development is necessary for large and medium-sized cities because they face two globalized phenomena: population growth and the concentration of people in urban centers. These phenomena create additional challenges for managers and impose the intelligent use of the city and its resources, focusing on the citizen. The search for efficiency in Smart and Human City (SHC) justifies the interest in technological solutions that support the digital transformation of society. The general objective of this work is to propose a strategy of local management of sociology-technical networks to foster the implementation of SHC. To this end, research was conducted with medium and large cities in Brazil using various research methods (exploratory-descriptive, survey-research and participant-research) that converged to the results that indicated: the growth of municipal insertion in the national agenda ST&I; confirmation of the interest of Brazilian medium-sized cities in the implementation of SHC (or related nomenclatures) and; the institutional dependence on an effective social and technological network committed to the concept of SHC. The use of social technologies based on studies in the Science, Technology, and Society (STS) is also recommended, especially the notion of Collective Intelligence and Actor-Network Theory (ANT), given the complex nature of a distributed network. The theoretical foundations are important to understand the translation of interests between stakeholders, which motivates and stimulates the development of the sociology-technical network. ANT seeks to better understand and explain the hybrid (social and technological) interactions that make it possible to stabilize and disseminate technical-scientific advances that influence behavior and life in society, which can result in a smarter, more human city.
Proposal for local management of socio-technical networks: strategy for the implementation of Intelligent and Human Cities
Keywords: Cidade inteligente; Cidade humana; Rede sociotécnica; Smart city; Intelligent cities; Human cities; Digital city; Sociology-technical network; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL